2020
DOI: 10.3390/ijms21082671
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Dermatitis: Identification and Management of Complicating Factors

Abstract: Atopic dermatitis (AD) is a chronic relapsing inflammatory skin disease, associated with impaired skin barrier function and an atopic background. Various complicating factors, such as irritants, aeroallergens, food, microbial organisms, contact allergens, sweat, and scratching can induce the development of AD symptoms. Irritants, including soap/shampoo and clothes, can cause itching and eczematous lesions. In addition, young children with AD tend to become sensitized to eggs, milk, or peanuts, while older chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 105 publications
2
37
0
5
Order By: Relevance
“…neurodermatitis) is one of the most common and chronic human inflammatory skin diseases whose pathogenesis remains insufficiently clear and for which no curative therapy is currently available. [1][2][3] As a key representative of the small group of so-called "atopic" diseases, AD carries a high burden of disease for affected individuals and their families, and is often triggered or aggravated by psychoemotional stress. 4,5 Since AD steadily increases in incidence and absorbs major health care resources, the development of optimized AD therapeutics that combine efficiency with long-term safety and affordability, especially for children with AD, 6 remains a major unmet challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…neurodermatitis) is one of the most common and chronic human inflammatory skin diseases whose pathogenesis remains insufficiently clear and for which no curative therapy is currently available. [1][2][3] As a key representative of the small group of so-called "atopic" diseases, AD carries a high burden of disease for affected individuals and their families, and is often triggered or aggravated by psychoemotional stress. 4,5 Since AD steadily increases in incidence and absorbs major health care resources, the development of optimized AD therapeutics that combine efficiency with long-term safety and affordability, especially for children with AD, 6 remains a major unmet challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Atopic dermatitis (AD; syn. neurodermatitis) is one of the most common and chronic human inflammatory skin diseases whose pathogenesis remains insufficiently clear and for which no curative therapy is currently available 1‐3 . As a key representative of the small group of so‐called “atopic” diseases, AD carries a high burden of disease for affected individuals and their families, and is often triggered or aggravated by psychoemotional stress 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The dosage of sulphite used in this study resulted in the initiation of epidermal hyperplasia in 10 days; furthermore, the extent of the epidermal hyperplasia was comparable to the protection induced by the more complex and concentrated ambient air pollutants that we explored in our previous study ( Chiu et al., 2020 ). Although epidermal hyperplasia is a key feature for diseases, such as atopic dermatitis and psoriasis, the pathological change of the skin is a manifestation caused by inflammatory stimuli originating from inside the body ( Tamagawa-Mineoka and Katoh, 2020 ). Sweat and environmental chemicals, such as air pollutants, are two of the complicating factors of atopic dermatitis ( Tamagawa-Mineoka and Katoh, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although epidermal hyperplasia is a key feature for diseases, such as atopic dermatitis and psoriasis, the pathological change of the skin is a manifestation caused by inflammatory stimuli originating from inside the body ( Tamagawa-Mineoka and Katoh, 2020 ). Sweat and environmental chemicals, such as air pollutants, are two of the complicating factors of atopic dermatitis ( Tamagawa-Mineoka and Katoh, 2020 ). The results of the present study revealed that both factors were able to induce the expression of proinflammatory cytokines in dermal fibroblasts; this likely contributes to the symptoms of dermatitis, which is an observation that has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[ 60 ] A Th1‐prone subtype as well as presence of contact allergy (especially to metals) is far more frequent in intrinsic AD. [ 61 ] Interestingly, intrinsic AD also shows more overlaps with psoriasis (including Th1 and Th17/22 dominance) than with extrinsic AD. [ 52 ] Further evidence for a rather small causative effect of IgE comes from AD mouse models, which are typically independent of IgE and B cells.…”
Section: Is There a Role For Mrgprx2 In Atopic Dermatitis?mentioning
confidence: 99%